2013
DOI: 10.1177/2278533720130104
|View full text |Cite
|
Sign up to set email alerts
|

Research on Work- Family Balance: A Review

Abstract: In the current globalized era, an increasing number of firms in the services sector require employees to work longer, frequently interact with customers and work across varied time zones. This has resulted in dilation of the boundary between work and family. This review explores the meaning, antecedents, consequences and moderators of work - family balance from conflict as well as enrichment perspectives. Further, the paper discusses the role of turn over intentions which have given mixed results in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 28 publications
1
24
0
2
Order By: Relevance
“…Descriptive statistics and intercorrelations between the measures are shown in Table 1; point biserial correlations were computed for dichotomously scored variables. As reported in other studies (Beutell, 2010;Dilworth & Kingsbury, 2005;Jain & Nair, 2013), gender, having a partner, education, and work hours (both those worked at the organization and those worked a home), showed some degree of association with either the independent of dependent variables of interest. We therefore controlled for these demographic variables in all subsequent analyses.…”
Section: Resultssupporting
confidence: 77%
“…Descriptive statistics and intercorrelations between the measures are shown in Table 1; point biserial correlations were computed for dichotomously scored variables. As reported in other studies (Beutell, 2010;Dilworth & Kingsbury, 2005;Jain & Nair, 2013), gender, having a partner, education, and work hours (both those worked at the organization and those worked a home), showed some degree of association with either the independent of dependent variables of interest. We therefore controlled for these demographic variables in all subsequent analyses.…”
Section: Resultssupporting
confidence: 77%
“…An attempt was made to identify the proximal antecedents of WFB, such as job and family satisfaction, as well as the several factors that influenced WFE and WFC, in turn strongly associated constructs directly and indirectly linked to WFB [ 8 , 9 , 10 , 20 ]. Moreover, this study examined if the hypothesized associations between variables may be different in relation to CSE since in the work-family literature, personality factors are salient [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bhargava and Baral [ 19 ] identified supervisor support and other job characteristics (e.g., job autonomy and variety), while Lo Presti et al found work-family organizational support to be an antecedent of WFE [ 21 ]. Hence, social support is an important antecedent of both directions (FWE and WFE), and co-worker support and workload seem to be fundamental variables that can either favor or hinder FWE development [ 35 , 36 ]. In short, while resources can either facilitate or enrich their subsequent job experiences [ 37 ], demands, on the other hand, can prevent and contrast enrichment, in turn generating conflict between the job and family domains.…”
Section: Theoretical Foundationmentioning
confidence: 99%
See 2 more Smart Citations